Diagnosis and management of central sleep apnea syndrome. (3rd June 2019) - Baillieul, Sébastien; Revol, Bruno; Jullian-Desayes, Ingrid; Joyeux-Faure, Marie; Tamisier, Renaud; Pépin, Jean-Louis
ABSTRACT: Introduction : Central sleep apnea (CSA) syndrome has gained a considerable interest in the sleep field within the last 10 years. It is overrepresented in particular subpopulations such as patients with stroke or heart failure. Early detection and diagnosis, as well as appropriate treatment of central breathing disturbances during sleep remain challenging. Areas covered : Based on a systematic review of CSA in adults the clinical evidence and polysomnographic patterns useful for discerning central from obstructive events are discussed. Current therapeutic indications of CSA and perspectives are presented, according to the type of respiratory disturbances during sleep, alterations in blood gases and ventilatory control. Expert opinion : The precise identification of central events during polysomnographic recording is mandatory. Therapeutic choices for CSA depend on the typology of respiratory disturbances observed by polysomnography, changes in blood gases and ventilatory control. In CSA with normocapnia and ventilatory instability, adaptive servo-ventilation is recommended. In CSA with hypercapnia and/or rapid-eye movement sleep hypoventilation, non-invasive ventilation is required. Further studies are required as strong evidence is lacking regarding the long-term consequences of CSA and the long-term impact of current treatment strategies.